Comparative analysis of forest buffalo grouping patterns in Central Africa - Melletti, Mario, author; Groenenberg, Milou, author; Breuer, Thomas, author; Turkalo, Andrea K., author; Hogg, Forrest, author; Ekouoth, Davy, author; Korte, Lisa, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
Understanding the social organization of elusive forest-dwelling ungulates may have important conservation and management implications. We present a comparison of grouping patterns in forest buffalo across different sites and through time in Central African rainforest. We examined five sites: Mbeli Bai and Bonye Bai (Nouabalé-Ndoki National Park, Republic of Congo), Dzanga Bai and Bai-Hokou (Dzanga-Ndoki National Park, C.A.R.) and Lopé-Okanda National Park (Gabon).Buffalo showed high site fidelity to open areas, including forest clearings. Forest buffalo herds (mean 12 ind. ± SD; range 3-24) were much smaller than records of savanna buffalo herds (mean 350 ind. ± SD; range 12-1500>), but also showed frequently fission-fusion patterns. Data from Mbeli Bai collected from 2012 to 2016confirm a stable presence of two buffalo herds (range 9-10 ind.) with occasional visits by lone individuals. Observations from Dzanga Bai over a period of 10 years (2006-2016) confirm the occurrence of only one buffalo herd (range 8-10ind.). In Bai-Hokou site, a single buffalo herd increased from 16 to 24 individuals during a three year period (2001-2004). Finally in Lopé National Park (a mosaic of savanna and forest fragments), the mean group size for 18 herds monitored from2002 to 2004 was 12±2 ind. (range of means=3–24). We analysed if herd size and herd stability are affected by clearing size, clearing type (e.g. marsh or land) and grass coverage across different sites and through time.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia in conjuction with the IUCN 2nd African Buffalo Symposium.